2021
DOI: 10.1080/08998280.2021.1897341
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection and severe rhabdomyolysis

Abstract: Although patients with COVID-19 can have mild nonspecific myalgia and mild elevation of creatinine kinase levels, severe myalgia along with elevation of creatinine kinase levels >10 times the upper normal limit and dark-colored urine indicate an underlying severe rhabdomyolysis. This report describes a 60-year-old morbidly obese man who was found to have severe rhabdomyolysis, along with acute kidney injury, dark-colored urine, and a positive COVID-19 test. He had a prolonged hospital course requiring continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Viral infection is a recognized cause of rhabdomyolysis which often initially presents with myalgias. Similar cases of rhabdomyolysis associated with COVID-19 infection have been reported in the literature beginning in the early months of the pandemic [4][5][6][7][8][9][10][11][12][13]. Our report demonstrates a case of rhabdomyolysis with an extremely high CK value that was treated with a high flow rate of IV fluids and resolved completely with no residual kidney disease and no need for hemodialysis during treatment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Viral infection is a recognized cause of rhabdomyolysis which often initially presents with myalgias. Similar cases of rhabdomyolysis associated with COVID-19 infection have been reported in the literature beginning in the early months of the pandemic [4][5][6][7][8][9][10][11][12][13]. Our report demonstrates a case of rhabdomyolysis with an extremely high CK value that was treated with a high flow rate of IV fluids and resolved completely with no residual kidney disease and no need for hemodialysis during treatment.…”
Section: Discussionsupporting
confidence: 82%
“…Viral infection is a recognized cause of rhabdomyolysis, which often initially presents with myalgias, as many viruses also do without concurrent rhabdomyolysis [1]. Numerous case studies have specifically reported associations between COVID-19 infection and rhabdomyolysis [4][5][6][7][8][9][10][11][12][13][14]. Thus, it is important to monitor COVID-19 patients with appropriate physical exams and labs in order to diagnose rhabdomyolysis early, initiate treatment, and mitigate downstream effects of proteinemia and myoglobinuria, such as acute kidney injury [1].…”
Section: Introductionmentioning
confidence: 99%
“…We recommend vaccinating lipin-1-deficient patients with all available vaccines, as the risk of decompensation is very high during epidemics of viral disease, and corticosteroids can make chickenpox worse. We include the vaccination against COVID-19, 22 although PAP-1 deficiency significantly suppresses SARS-CoV-2 replication 23 and this vaccine can be responsive for RM. 24 The innate immune system acts as the first line of defense against invading pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been well documented case reports of COVID-19 related rhabdomyolysis ( Alrubaye and Choudhary, 2020 ; Chan et al, 2020 ; Husain et al, 2020 ; Khosla et al, 2020 ; Meegada et al, 2020 ; Mukherjee et al, 2020 ; Rivas-García et al, 2020 ; Rosato et al, 2020 ; Singh et al, 2020 ; Byler et al, 2021 ; Haroun et al, 2021 ; Mah et al, 2021 ; Patel et al, 2021 ). Rhabdomyolysis is a skeletal muscle injury that can result in acute kidney injury, a life-threatening clinical complication.…”
Section: The Musculoskeletal Symptomatologymentioning
confidence: 97%